Estimated Effects of Early Diuretic Use in Critical Illness. (July 2019) - McCoy, Ian E.; Montez-Rath, Maria E.; Chertow, Glenn M.; Chang, Tara I.
Abstract : Objectives: To estimate the effects of diuretic use during the first 24 hours of an ICU stay on in-hospital mortality and other clinical outcomes including acute kidney injury and duration of mechanical ventilation. Design: Retrospective cohort study. Setting: Urban, academic medical center. Patients: Adult patients admitted to medical or cardiac ICUs between 2001 and 2012, excluding those on maintenance dialysis or with ICU length of stay less than 24 hours. Interventions: None. Measurements and Main Results: We included 13, 589 patients: 2, 606 with and 10, 983 without early diuretic use (loop diuretic exposure during the first 24 hr of an ICU stay). Propensity score matching generated 2, 523 pairs with well-balanced baseline characteristics. Early diuretic use was unassociated with in-hospital mortality (risk ratio, 1.01; 99.5% CI, 0.83–1.22). We found no evidence of associations with ICU or hospital length of stay, or duration or provision of mechanical ventilation. Early diuretic use was associated with higher rates of subsequent acute kidney injury (risk ratio, 1.41; 99.5% CI, 1.25–1.59) and electrolyte abnormalities. Results were not materially different in subgroups of patients with heart failure, chronic kidney disease, or acute lung injury. Conclusions: Early diuretic use in critical illness was unassociated with in-hospital mortality, ICU or hospital length of stay, or duration of mechanical ventilation, but risks of acute kidney injury and electrolyte abnormalities were higher. Abstract : Supplemental Digital Content is available in the text.